Marginalized identities, mistreatment, discrimination, and burnout among US medical students: cross sectional survey and retrospective cohort study. (22nd March 2022) - Teshome, Bethelehem G; Desai, Mayur M; Gross, Cary P; Hill, Katherine A; Li, Fangyong; Samuels, Elizabeth A; Wong, Ambrose H; Xu, Yunshan; Boatright, Dowin H
Abstract: Objective: To describe the association between mistreatment, burnout, and having multiple marginalized identities during undergraduate medical education. Design: Cross sectional survey and retrospective cohort study. Setting: 140 US medical schools accredited by the Association of American Medical Colleges. Participants: 30 651 graduating medical students in 2016 and 2017. Main outcome measures: Self-reported sex, race or ethnicity, and sexual orientation groups were considered, based on the unique combinations of historically marginalized identities held by students. Multivariable linear regression was used to determine the association between unique identity groups and burnout along two dimensions (exhaustion and disengagement) as measured by the Oldenburg Burnout Inventory for Medical Students while accounting for mistreatment and discrimination. Results: Students with three marginalized identities (female; non-white; lesbian, gay, or bisexual (LGB)) had the largest proportion reporting recurrent experiences of multiple types of mistreatment (88/299, P<0.001) and discrimination (92/299, P<0.001). Students with a higher number of marginalized identities also had higher average scores for exhaustion. Female, non-white, and LGB students had the largest difference in average exhaustion score compared with male, white, and heterosexual students (adjusted mean difference 1.96, 95% confidence interval 1.47 to 2.44). Mistreatment and discrimination mediated exhaustion scores for all identity groups but did not fully explain the association between unique identity group and burnout. Non-white and LGB students had higher average disengagement scores than their white and heterosexual counterparts (0.28, 0.19 to 0.37; and 0.73, 0.52 to 0.94; respectively). Female students, in contrast, had lower average disengagement scores irrespective of the other identities they held. After adjusting for mistreatment and discrimination among female students, the effect among female students became larger, indicating a negative confounding association. Conclusion: In this study population of US medical students, those with multiple marginalized identities reported more mistreatment and discrimination during medical school, which appeared to be associated with burnout.